Boosting Bifunctional Oxygen Electrolysis for N‐Doped Carbon via Bimetal Addition. Issue 16 (15th February 2017) - Wang, Jian; Ciucci, Francesco
Abstract : The addition of transition metals, even in a trace amount, into heteroatom‐doped carbon (M‐N/C) is intensively investigated to further enhance oxygen reduction reaction (ORR) activity. However, the influence of metal decoration on the electrolysis of the reverse reaction of ORR, that is, oxygen evolution reaction (OER), is seldom reported. Moreover, further improving the bifunctional activity and corrosion tolerance for carbon‐based materials remains a big challenge, especially in OER potential regions. Here, bimetal‐decorated, pyridinic N‐dominated large‐size carbon tubes (MM′‐N/C) are proposed for the first time as highly efficient and durable ORR and OER catalysts. FeFe‐N/C, CoCo‐N/C, NiNi‐N/C, MnMn‐N/C, FeCo‐N/C, NiFe‐N/C, FeMn‐N/C, CoNi‐N/C, MnCo‐N/C, and NiMn‐N/C are systematically investigated in terms of their structure, composition, morphology, surface area, and active site densities. In contrast to conventional monometal and N‐decorated carbon, small amounts of bimetal (≈2 at%) added during the one‐step template‐free synthesis contribute to increased pyridinic N content, much longer and more robust carbon tubes, reduced metal particle size, and stronger coupling between the encapsulated metals and carbon support. The synergy of those factors accounts for the dramatically improved ORR and OER activity and stability. By comparison, NiFe‐N/C and MnCo‐N/C stand out and achieve superior bifunctional oxygen catalytic performance, exceeding most of state‐of‐the‐art catalysts. Abstract : Bimetal addition is found to contribute to increased pyridinic N content, much longer and more robust carbon tube, reduced metal particle size, and stronger coupling between the remained metal and carbon support. The proposed new framework, that is, bimetal‐decorated, pyridinic N‐dominated, large‐size carbon tubes (MM′‐N/C), achieves superior bifunctional oxygen reduction reaction and oxygen evolution reaction catalytic performance.